Understanding the Role of Toll-Like Receptors 9 in Breast Cancer - Al-alem, Umaima; Al-Saruri, Alaa; Bamahros, Hasan; Mahmoud, Abeer M.; Sible, Emily; Hasan, Uzma A. (Cancers, 2024)
Breast cancer is a significant global issue, ranking as the second most common cancer among women worldwide and a leading cause of cancer-related deaths. Although the exact causes of this increase remain unclear, factors such as genetics, epigenetics, obesity, sedentary lifestyle, tobacco use, and vitamin D deficiency have been implicated. The Toll-like receptor 9 (TLR9) is recognized for its role in inflammation and innate immunity; however, its specific involvement in breast cancer pathogenesis requires further investigation. This study aims to systematically review the existing literature on TLR9 expression in normal and cancerous breast tissue, providing current knowledge and identifying gaps. Relevant articles in English were from PubMed, Scopus, and Google Scholar, with the inclusion criteria focusing on studies evaluating TLR9 mRNA and protein expression. The review found that TLR9 mRNA and protein exhibit variable expressions in both normal and cancerous breast tissue, highlighting the need for further research to clarify TLR9’s role in breast cancer.
CRIS-Team Scopus Importer:2024-08-16
Keywords: breast cancer; systematic review; Toll-like receptor 9